Moravianism as One of the Themes Redefining Czech Literature After the Political Changes of 1989 - Németh Vítová, Lenka (Porównania, 2024)
The author presents selected works by Czech writers associated with the Moravian region and published after the political changes of 1989 (Ota Filip, Jiří Kratochvil, Antonín Bajaja, Alena Mornštajnová, Kateřina Tučková, Jan Balabán) and highlights how the theme of “Moravianism” in Czech literature not only revealed new possibilities for incorporating elements of authenticity but, more importantly, restored the reputation of the previously profaned concept of literary engagement, and gave renewed relevance – appropriate for the era of freedom – to the concept of agency of literary works.